NASI SAMIN SEBAGAI DAYA TARIK WISATA KULINER DI KABUPATEN INDRAGIRI HILIR - Yolanda, Risma; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The development of global tourism has shown rapid changes, marked by the emergence of new destinations, increasingly comprehensive facilities, and safe and comfortable transportation. One growing trend is culinary tourism, which utilizes a region's unique food or beverages as a diplomatic tool to introduce the area. Nasi Samin, a traditional dish from Indragiri Hilir Regency, stands out as a major attraction in the culinary tourism sector of Tembilahan. Nasi Samin is more than just a dish; it represents cultural heritage that reflects the long history of cultural interactions in Indonesia. By retaining traditional elements from Palembang and adapting them to local tastes, Nasi Samin has become a significant dish in the culinary traditions of Tembilahan's community. This research aims to describe Nasi Samin as a culinary tourism attraction in Indragiri Hilir Regency and illustrate its role in local economic development. A qualitative research method with a descriptive approach was employed to observe and explain the phenomenon by gathering data and information in the field. The study findings reveal that Nasi Samin is presented in four variations, including the types of food, preparation and cooking methods, and the tools used in the processing and serving. Furthermore, the research highlights the significant role of Nasi Samin as a culinary tourism attraction in Indragiri Hilir Regency. Keywords: Nasi Samin, Tourism Attraction, Culinary Tourism